Comparison of two stitches versus one stitch for emergency cervical cerclage to prevent preterm birth in singleton pregnancies. Issue 1 (21st April 2022) - Xu, Zhi‐Min; Zhang, Jun; Hong, Xiao‐Lan; Liu, Jing; Yang, Zhen‐Zhen; Pan, Mian
Abstract: Objective: To compare the efficacy of two stitches versus one stitch in women with emergency cervical cerclage. Methods: A retrospective case–control study of 26 women with singleton pregnancies who underwent emergency cervical cerclage before 26 weeks. A comparison was made between patients with two stitches versus one stitch at the time of cervical cerclage placement. The primary outcome was gestational age (GA) at delivery and preterm birth (PTB) before 37, 34, 32, 28, and 24 weeks. Results: Average GA at delivery in the two‐stitches group was significantly greater than in the one‐stitch group (32.71 ± 5.54 weeks vs 27.99 ± 4.70 weeks, P = 0.028). There were significant decreases in the incidence of spontaneous PTB at <34 weeks and less than 32 weeks in the two‐stitches group ( P = 0.034; P = 0.013, respectively). The neonatal intensive care unit (NICU) admissions rate and length of stay in the NICU in the two‐stitches group were significantly reduced ( P = 0.035 and P = 0.018, respectively). However, there was no significant difference in neonatal mortality between the two groups. Conclusion: Compared with emergency cervical cerclage placement with one stitch, the procedure with two stitches can prolong the pregnancy and improve the neonatal prognosis more effectively.